2018
DOI: 10.1002/csr.1519
|View full text |Cite
|
Sign up to set email alerts
|

Consumers' heterogeneous preferences for corporate social responsibility in the food industry

Abstract: This study reveals the consumer side of corporate social responsibility (CSR) in the food industry, exploring awareness, preferences and willingness to pay for CSR of a representative sample of Italian households. The results clearly indicate that Italian consumers reveal a high level of awareness within clear, though heterogeneous, preferences for CSR initiatives. Five consumers' groups were identified: ‘environmentalists’, ‘pro‐socials’, ‘collectivists’, ‘animal friends’ and ‘selfish health centered’. Furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 83 publications
(182 reference statements)
5
42
1
Order By: Relevance
“…Hence, the adoption of CSR practices, as a nexus among various business operations, can strengthen the buying tendencies of consumers to achieve firms' goals and to influence consumer behavior significantly. Our findings are consistent with those of previous studies, in which academicians and practitioners concluded that CSR activities are extremely important by confirming their considerable impact on consumers' preferences, attitudes, and behaviors worldwide (e.g., Boccia & Sarnacchiaro, ; S. B. Choi et al, ; Hur et al, ; Jones III et al, ; Lerro et al, ; Ramesh et al, ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Hence, the adoption of CSR practices, as a nexus among various business operations, can strengthen the buying tendencies of consumers to achieve firms' goals and to influence consumer behavior significantly. Our findings are consistent with those of previous studies, in which academicians and practitioners concluded that CSR activities are extremely important by confirming their considerable impact on consumers' preferences, attitudes, and behaviors worldwide (e.g., Boccia & Sarnacchiaro, ; S. B. Choi et al, ; Hur et al, ; Jones III et al, ; Lerro et al, ; Ramesh et al, ).…”
Section: Discussionsupporting
confidence: 92%
“…From the marketing and consumer perspectives, a multidimensional and deep analysis is needed to verify the benefits and identify the nexus between CSR practices and buying tendencies. In particular, empirical testing is required in manifold regions to clarify how the acceptance of CSR practices may influence BBTs in different economies(e.g., S. B. Choi, Feng, Liu, & Zhu, ; Jones III, Reilly, Cox, & Cole, ; Lerro, Vecchio, Caracciolo, Pascucci, & Cembalo, ; Ramesh, Saha, Goswami, & Dahiya, ).…”
Section: Introductionmentioning
confidence: 99%
“…CSP should positively affect firms' top‐line performance if it increases the quantities sold and/or the prices customers are willing to, or actually, pay. Evidence from numerous surveys and experiments suggests that this might be the case in consumer markets (Du, Bhattacharya, & Sen, ; Lerro, Vecchio, Caracciolo, Pascucci, & Cembalo, ; Lii, Wu, & Ding, ; Trudel & Cotte, ). According to these studies, the relationship between CSP and the top‐line performance of B2C firms should be positive.…”
Section: Conceptual Background and Hypothesesmentioning
confidence: 99%
“…Even though some concerns regarding these issues began to spread in the 1930s and 1940s, the analysis of company approaches to social responsibility tends to consider more developed and recent versions of the concept, starting from the 1950s to 1960s (Carroll, 1999). In the last decades, it has gained momentum, as consumers are becoming more aware and concerned about the environmental and social impacts of economic activities (Lerro, Vecchio, Caracciolo, Pascucci, & Cembalo, 2018).…”
Section: Csr and Sustainability Reportingmentioning
confidence: 99%